A Lattice Boltzmann Model to Study Sedimentation Phenomena in Irrigation Canals (Communications in Computational Physics, 2020)
Fresh water is one of the most significant resources for human activities andsurvival, and irrigation is among the most important uses of water. The sustainibilityand performance of irrigation canals can be greatly affected by sediment transport anddeposition. In our previous works, we proposed a Lattice Boltzmann model for simulating a free surface flow in an irrigation canal, as an alternative to more traditionalmodels mainly based on shallow water equations. Here we introduce the sedimentation phenomenon into our model by adding a new algorithm, based on the earlierwork by B. Chopard, A. Dupuis and A. Masselot [9, 11, 12, 27]. Transport, erosion,deposition and toppling of sediments are taken into account and enable the globalsedimentation algorithm to simulate different transport modes such as bed load andsuspended load. In the present work, we study both the behaviour of a sediment deposit located at an underflow submerged gate (depending on the gate opening and theflow discharge) and the influence of the presence of such a deposit on the flow. Bothnumerical and experimental validations have been performed. The experiments wererealized on the micro-canal of the LCIS laboratory at Valence, France. The comparisonsbetween simulations and experiments give good qualitative agreement.